Investigation on behaviour of simply supported unbonded post-tensioned beams - Krishnan, M. A. Deepak; Sengupta, Amlan K. (Journal of Structural Engineering, 2024)
An analysis procedure was developed to predict the moment versus rotation behaviour in the vicinity of the critical section of a simply supported beam, post-tensioned with unbonded tendons. For the post-cracking behaviour, the procedure was developed based on the concept of plastic zone of concrete deformation. The procedure satisfies not only the equilibrium condition, but also the compatibility of deformation of the tendons and the concrete, and the stress versus strain curves of the materials. The results for a few specimens from the literature on the above type of beams are presented. It was observed that the proposed procedure can reasonably predict the behaviour of a specimen up to failure. Finally, a parametric study was conducted to study the effects of the important design variables on the response of beams posttensioned with unbonded tendons.